2022
DOI: 10.1039/d2cp01667b
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach to the ion recognition mechanism of K+ channels from laser spectroscopy of hydrated partial peptide–alkali metal ion complexes

Abstract: K+ channels allow selective permeation of K+, but not physiologically abundant Na+, at almost diffusion limit rates. The conduction mechanism of K+ channels is still controversial, with experimental and computation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, as the next plan, a budget request is being made for the development of a new operand light scattering imaging apparatus to establish an evaluation method for mesoscopic areas, especially in chemistry and biology, toward the evaluation of functions and properties of various material groups. Other results related to electronic structure studies taken by UVSOR-III are found in the literatures [28][29][30][31][32][33][34][35][36][37][38]. In figure 2, the list of our beamlines is shown.…”
Section: History Of Uvsormentioning
confidence: 83%
“…In addition, as the next plan, a budget request is being made for the development of a new operand light scattering imaging apparatus to establish an evaluation method for mesoscopic areas, especially in chemistry and biology, toward the evaluation of functions and properties of various material groups. Other results related to electronic structure studies taken by UVSOR-III are found in the literatures [28][29][30][31][32][33][34][35][36][37][38]. In figure 2, the list of our beamlines is shown.…”
Section: History Of Uvsormentioning
confidence: 83%
“…IRPD spectroscopy was also performed in order to record the IR signature of all possible conformers populated in the cold ion trap at once. The IRPD spectra of the hydrated clusters of DAH + /TrpH + have been obtained through a 2-color scheme . The first laser (IR1) illuminated the ions in the QIT ∼ 50 ns prior to the second laser (IR2) irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous vibrational studies targeting the interplay of non-covalent interactions in model systems for biomolecules in the gas phase. Examples include the structural analysis of oligosaccharides, 14,15 lipids, 16,17 metal ion-amino acid and -peptide complexes, 12,[18][19][20][21][22][23][24][25] studies of model peptides for the selectivity filter of potassium ion channels, [26][27][28] solvation studies of biomolecules, [29][30][31][32][33] and solvent-induced protomer switching, [34][35][36][37] to name just a few.…”
Section: Introductionmentioning
confidence: 99%